2014
DOI: 10.1097/pep.0000000000000046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Virtual Reality on Upper Extremity Function in Children With Cerebral Palsy

Abstract: Virtual reality is a viable tool to improve UE function in children with CP. However, a more vigorous research design is needed to make a conclusive recommendation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 41 publications
0
68
1
5
Order By: Relevance
“…Recent systematic reviews consider constraint‐induced movement therapy as an effective intervention; however, future research is needed to establish the efficacy of various models and dosages . The use of neuromuscular electrical stimulation, virtual reality, and parent education and counselling are consistent with the recent evidence; but future research is needed to make conclusive recommendations. There is limited‐to‐no evidence for the use of myofascial release, sensory integration, suit therapy, and proprioceptive neurofacilitation techniques in children with CP, and it is suggested that these techniques should not be used .…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews consider constraint‐induced movement therapy as an effective intervention; however, future research is needed to establish the efficacy of various models and dosages . The use of neuromuscular electrical stimulation, virtual reality, and parent education and counselling are consistent with the recent evidence; but future research is needed to make conclusive recommendations. There is limited‐to‐no evidence for the use of myofascial release, sensory integration, suit therapy, and proprioceptive neurofacilitation techniques in children with CP, and it is suggested that these techniques should not be used .…”
Section: Discussionmentioning
confidence: 99%
“…13,86,87,14,88,15,89, 85,90 The nine systematic reviews were completed between 2009–2015 and varied in focus. (Table 1) Within the reviews, there were 12 randomized controlled trials (RCT) and 85 other types of intervention studies suggesting a relatively large amount of research on VR and SG in pediatrics.…”
Section: Outcomes Of Vr and Sg Interventionsmentioning
confidence: 99%
“…Customized systems are superior to SG in balance and mobility studies in people post-stroke and with upper extremity function in children with CP. 89,103 One problem with these customized systems is that many are developed and tested and then discarded because no method exists to transfer them out of the lab and into the clinic. To address this gap, clinician scientists and engineers from Spain, Portugal and the US have created an online resource, Open Rehabilitation Initiative, to share executable versions of the VR and SGs.…”
Section: Bridging the Gap From Evidence To Practicementioning
confidence: 99%
“…A review of interactive computer play for individuals with CP reported a moderate level of evidence for improved gross motor outcomes yet inconclusive evidence for upper limb motor function . A meta‐analysis examining the effect of specific virtual reality technologies in children with CP found a strong effect on upper limb function . Young children were identified as the best responders, and engineer‐built virtual reality systems had a greater effect than commercially available systems .…”
mentioning
confidence: 99%